How does level of personality functioning inform clinical management and treatment? Implications for ICD-11 classification of personality disorder severity. Issue 1 (January 2021) - Bach, Bo; Simonsen, Sebastian
Abstract : Purpose of review: The International Classification of Diseases, 11th Edition (ICD-11) classifies personality disturbance according to levels of severity. This article reviews the literature on levels of personality functioning in relation to clinical management and treatment, and proposes how these findings apply to the ICD-11 classification of personality disorders. Recent findings: Findings were primarily derived from studies using the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) Level of Personality Functioning Scale (LPFS), Kernberg's Level of Personality Organization, and the general P -factor of personality disorder. Severity of personality dysfunction is related to treatment outcome, risk of dropout, therapeutic alliance, readiness for treatment, risk of harm to self or others, risk of dissociation and psychotic-like breaks, coherence in narrative identity, reflective functioning, and epistemic trust. Summary: The overall level of personality disorder severity indicates risk of negative outcomes and may be used as decision tool for 'personalized medicine' and required treatment intensity (e.g., strength of alliance and the need for establishing epistemic trust). Beyond the ICD-11 guidelines for determining personality disorder severity, these implications also apply to practitioners using comparable frameworks such as the DSM-5 LPFS and Kernberg's Level of Personality Organization. Future research should focus on the interaction of severity with trait qualifiers in relation to clinical management.